Choreography of Hoyak Baindang Dance in Sanggar Abai Sakato Nagari Abai, Sangir Batang Hari District - Maghdalena Tri Jureta; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to reveal and describe the results of the presentation of Hoyak Baindang Dance Choreography art at the Abai Sakato Art Studio in Nagari Abai, Sangir Batang Hari District by using qualitative research which proposes a descriptive method. To collect research data, observations, interviews and documentation must be carried out. The object of this research is the Hoyak Baindang Dance and this research shows how the dance movements have Minang Malay movements which are firm and also contain Malay elements. The movement that comes to mind in the choreography's imagination is also stimulated by the expression and enthusiasm produced by the choreography. In the movement there is also music and also the spirit of the dancers in bringing the atmosphere that is in the Hoyak Baindang dance, the property in this dance also uses a small tambourine which is played by the dancers, and still follows Islamic law "Adat Ba Sandi Syarak, Syarak Ba Sandi Kitabullah”.